Arterial Stiffness, Biomarkers of Liver Fat, and the Development of Metabolic Dysfunction in Metabolically Healthy Population: A Prospective Study - Lin, Lin; Wang, Long; Du, Rui; Hu, Chunyan; Lu, Jieli; Wang, Tiange; Li, Mian; Zhao, Zhiyun; Xu, Yu; Xu, Min; Bi, Yufang; Wang, Weiqing; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Metabolic dysfunction is known to be associated with arterial stiffness. However, the risks of metabolic syndrome and diabetes due to arterial stiffness and the potential mechanism remain unclear. We aimed to investigate the association of arterial stiffness with the risk of metabolic syndrome and diabetes, and determine whether this association is mediated by liver fat. Methods: A prospective study was conducted with 4139 Chinese adults who were metabolically healthy at baseline. Arterial stiffness was measured by brachial–ankle pulse wave velocity (baPWV). Obesity was defined as body mass index ≥25.0 kg/m2. The primary outcomes were incident metabolic syndrome and diabetes. Results: During a median follow-up of 4.4 years, 1022 (24.7%) and 354 (9.5%) participants developed metabolic syndrome and diabetes, respectively. Compared with those in the lowest quartile of baPWV, participants in the highest quartile had 85% and 91% higher risks of metabolic syndrome and diabetes [risk ratio (RR) 1.85, 95% confidence interval (CI) 1.41, 2.42 for metabolic syndrome; RR 1.91, 95% CI 1.16, 3.15 for diabetes). Mediation analyses indicated that fatty liver significantly mediated the association of arterial stiffness with metabolic syndrome and diabetes risk. Specifically, 18.4% of metabolic syndrome and 12.6% of diabetes risk due to arterial stiffness were mediated through fatty liver. Conclusions: Arterial stiffness was associated with higher risks of metabolic syndrome and diabetes in individuals with obesity. This association may be partially mediated by fatty liver.